Perspectives on masculinity, femininity and the South African military : gender relations with specific focus on the impact of the South African Army Women’s College and the SADF (1971-1998). - Kotze, Esté (Stellenbosch : Stellenbosch University, 2015)
Thesis (MA)--Stellenbosch Unversity, 2015.